Heterochromatic histone modifications at transposons in Xenopus tropicalis embryos - van Kruijsbergen, Ila (Dev Biol, 2016)
Transposable elements are parasitic genomic elements that can be deleterious for host gene function and genome integrity. Heterochromatic histone modifications are involved in the repression of transposons. However, it remains unknown how these histone modifications mark different types of transposons during embryonic development. Here we document the variety of heterochromatic epigenetic signatures at parasitic elements during development in Xenopus tropicalis, using genome-wide ChIP-sequencing data and ChIP-qPCR analysis. We show that specific subsets of transposons in various families and subfamilies are marked by different combinations of the heterochromatic histone modifications H4K20me3, H3K9me2/3 and H3K27me3. Many DNA transposons are marked at the blastula stage already, whereas at retrotransposons the histone modifications generally accumulate at the gastrula stage or later. Furthermore, transposons marked by H3K9me3 and H4K20me3 are more prominent in gene deserts. Using intra-subfamily divergence as a proxy for age, we show that relatively young DNA transposons are preferentially marked by early embryonic H4K20me3 and H3K27me3. In contrast, relatively young retrotransposons are marked by increasing H3K9me3 and H4K20me3 during development, and are also linked to piRNA-sized small non-coding RNAs. Our results implicate distinct repression mechanisms that operate in a transposon-selective and developmental stage-specific fashion.